Pengaruh Social Media Marketing Terhadap Keputusan Pembelian (Progress, 2025)
There are three major e-commerce platforms in Indonesia, namely Tokopedia, Shopee, and Lazada. These three e-commerce platforms compete to win the hearts of consumers. There are several factors that can influence purchasing decisions, one of which is social media marketing. Based on this background, the author is interested in conducting a study entitled The Influence of Social Media Marketing on Purchasing Decisions. The population in this study consists of consumers who have made purchases on Shopee, domiciled in Purworejo Regency, and have a Shopee application account. The exact number is unknown due to the lack of available data. The sample was taken using purposive sampling, totaling 100 respondents. Data analysis techniques used include simple linear regression, coefficient of determination, and t-test. The results of the simple linear regression test showed a constant value of 9.052 with an a b value of 0.947. The results of the coefficient of determination test showed an R square value of 51.8%. The results of the t-test show that the calculated t-value is greater than the t-table value (10.258 > 1.661) with a significance value of 0.000 (< 0.05).